2018
DOI: 10.1007/s00213-018-4856-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased suicide rates in recent antidepressant clinical trials

Abstract: RationaleThe last systematic analysis of suicidality in antidepressant clinical trials submitted for approval by the US Food and Drug Administration was in 2000. Given the attention to suicide and antidepressants in the early 2000s, the authors aimed to evaluate if there have been any changes in suicide rates in antidepressant clinical trials following 2000.Objective and MethodsThe Integrated Safety Summary data from approval packets for 14 investigational antidepressant programs (1991–2013, 40,857 patients, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 9 publications
0
26
1
6
Order By: Relevance
“…There is debate about the effectiveness of antidepressants in suicide prevention 76,77,78 . In a data linkage study covering 1989-1999 inclusive, Kelly and colleagues found that for adults aged 30 years and above, there was an inverse relationship between antidepressant prescribing and suicide 79 .…”
Section: Primary Care and Medication Usementioning
confidence: 99%
“…There is debate about the effectiveness of antidepressants in suicide prevention 76,77,78 . In a data linkage study covering 1989-1999 inclusive, Kelly and colleagues found that for adults aged 30 years and above, there was an inverse relationship between antidepressant prescribing and suicide 79 .…”
Section: Primary Care and Medication Usementioning
confidence: 99%
“…Many ecological studies including this study found that antidepressants have protective effects on suicidality (Nischal, Tripathi, Nischal, & Trivedi, 2012). A recent cohort study and randomized control trials advocate about the positive effects of antidepressants in the protection of suicides (Cheung et al, 2015; Khan, Fahl Mar, Gokul, & Brown, 2018). As shown by the previous study the suicidality might increase during the initial phase of treatment with antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these data suggest that the 'healthiest' of the population of depression and schizophrenic patients still died at higher rates than the 'healthiest' of the population of diabetes and hypertension patients in clinical trials. This is even more striking if one considers that suicidality, which is known to be associated with psychiatric illnesses, is systematically screened out of clinical trials such that potential patients who appear to be at higher risk of suicidal behaviour during the trial are excluded from participation (Khan et al 2018).…”
Section: Discussionmentioning
confidence: 99%